A study to set-up a technological process for purification of Zinc scraps by using liquation method - Tran, Ngoc Vuong; Luong, Manh Hung; Nguyen, Dinh Dang (Nuclear Science and Technology, 2018)
Zinc scrap is a source of raw material for zinc oxide production. However, to qualify the requirement of raw material for zinc oxide (99.5%) production, refining this source is needed. Many methods are considered such as rectification, chemical method, etc., but difficult to apply on an industrial scale. This workfocused on the investigation of the influence of temperature and time factors for asessing the possibility of applying liquation method for the purification of impurities from scrap zinc.The experiment results show that the optimum temperature of liquation to remove Pb,Fe from zinc scrap is in the range of 440-450°C, the optimal time of the process is 8h for the pot with 8cm in height and 6cm in diameter (the quantity of raw zinc sample is about 2kg / batch), then we can obtain about 80% of zinc metal with an average Zn content of about 97, 0%, both Pb and Fe content decreased to a range from 0.35 to 0.4%, and 1.0 to 1.1%, respectively, which meet the requirement of raw materials for the production of high quanlity ZnO ( 99,5 %). Based on the parameters obtained on lab-scale, a trial on pilot scale of 250 kg / batch was conducted, The result confirms that the quality of the products meets the requirement of raw materials for production of high quality ZnO (99.5%) and a technology process for refining zinc scrap by the liquation was proposed.